QUALITY INTEGRATION OF THE EDUCATIONAL PROCESS IN THE ACCOUNTING AND FINANCING OF THE ROMANIAN UNIVERSITIES - INTERESTS AND LIMITS - MARIANA MAN; MARIA CIUREA (Annals of the University of Petrosani: Economics)
The mission of Higher Education is to meet the specific needs of education and professional training of the citizens and also the needs of social-economic development of local and national communities. Universities carry out their mission only on the condition that they meet these needs to a quality standard which allows the individual and the society to become successful in a competitive and globalized environment. The present study intends to capture the relevant aspects of the integration mechanism of the quality of the educational process into the accounting and financing of Higher Education institutions.